Cyclooxygenase-2 expression in cervical cancer - Mandić, Aljoša; Ušaj-Knežević, Slavica; Ivković Kapicl, Tatjana; Ninčić, Dejan; Malenković, Goran (Vojnosanitetski pregled, 2014)
Background/Aim. Cyclooxygenase (COX) or prostaglandin H2 synthase is the first enzyme that catalyzes the first two steps in the biosynthesis of prostaglandins from arachidonic acid. The aim of the study was to determine the expression level of COX-2 in patients with cervical cancer and compare it with that in the control group with no cervical pathology. Methods. The study included 76 patients divided into two groups: the control group – 30 patients without histopathological changes and the group A – 46 patients with cervical cancer, FIGO stage IB-IIA. Histopathological and immunohistochemical analyses were performed in these two groups of patients. Results. In the control group, the expression of COX-2 was not confirmed compared to the group A of 26 (56.52%) patients. The expression of COX-2 showed a statistically significant difference in the presence of lymphocytic stromal infiltration (p = 0.0053). The expression of COX-2 was more pronounced in the stromal tissue without lymphocytic infiltration (80% vs 20%). Conclusion. A higher expression of COX-2 in cervical carcinoma without stromal lymphocytic infiltration suggests a possible paradoxical effect of COX-2 in immunosuppression. Frequent COX- 2 expression in the subgroup with poor prognostic histological parameters in the group A indicates the importance of COX-2 expression in the carcinogenesis of cervical cancer.
Keywords: uterine cervical neoplasms; prostaglandin-endoperoxide synthases; immunohistochemistry; gene expression; sensitivity and specificity